2011
DOI: 10.1016/j.indcrop.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fiber from tangerine juice industry

Abstract: The aim of this study was to assess the effect of several operational variables on both biological and separation process performance in a submerged anaerobic membrane bioreactor pilot plant that treats urban wastewater. The pilot plant is equipped with two industrial hollow-fiber ultrafiltration membrane modules 2 KeywordsBiogas production; hollow-fiber membrane; industrial membranes; submerged anaerobic membrane bioreactor; urban wastewater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…In the Turkish Food Codex it was indicated that pH value for extra traditional jam must be between 2.8 and 3.5 (Anonymous e , 2007). It was observed that the pH value for mandarin in this study was lower than those obtained by Del Caro et al (2004), Marti et al (2011), Harrison et al (2013). The low pH will contribute to high stability in the formulated jam.…”
Section: Resultscontrasting
confidence: 62%
“…In the Turkish Food Codex it was indicated that pH value for extra traditional jam must be between 2.8 and 3.5 (Anonymous e , 2007). It was observed that the pH value for mandarin in this study was lower than those obtained by Del Caro et al (2004), Marti et al (2011), Harrison et al (2013). The low pH will contribute to high stability in the formulated jam.…”
Section: Resultscontrasting
confidence: 62%
“…Previous authors have reported on the quantity and phytochemical properties of fibre found in OP and AP (Figuerola et al, 2005;Gorinstein et al, 2001;Grigelmo-Miguel and Martín-Belloso, 1999;Martí et al, 2010)). Much research has been carried out to study the bioactive (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The ADF and NDF composition data correlate with monosaccharide content in Glu concentration. The amounts of NDF and ADF were much higher than those measured from the fibre-rich by-products of other fruits such as the peel of mandarins [24].…”
Section: Discussionmentioning
confidence: 63%
“…Polysaccharide Characterization 2.6.1. Dietary Fibre Determination For the determination of dietary fibre, differentiation was made between total dietary fibre (TDF), acid detergent fibre (ADF), which indicates the amount of cellulose and lignin, and neutral detergent fibre (NDF), which in addition determines the amount of hemicellulose present in the sample and has been reported to be fermentable by the gut microbiota [22][23][24]. ADF and NDF were used as indicators of structural changes in persimmon dietary fibre after US-NADES treatment.…”
Section: Antioxidant Activitymentioning
confidence: 99%